4-Chloro-2-phenyl-2H-chromene-3-carbaldehyde - B. Punithavalli; A. Therasa Alphonsa (IUCrData)
The title compound, 4-chloro-2-phenyl-2H-chromene-3-carbaldehyde (PCC), C16H11ClO2, was obtained in good yield by a standard one-pot method. The molecule has the following substituents: a chlorine atom at the 4-position, a phenyl group at the 2-position, and an aldehyde (–CHO) group at the 3-position of the 2H-chromene ring system.